Proceso de ASC - IMPLEMENTACION DE UN SISTEMA DE HOLOGRAFIA DIGITAL A COLOR (2021)
This project aims to introduce the fundamentals and basic tools of digital holography to the semillero, starting from optical setup configuration, through digital recording using CCD sensors, to numerical reconstruction of the hologram on computer systems. The project proposes the development of a basic system for color digital holography using monochromatic illumination sources in the setup.